STATE OF PERIODONTAL TISSUES IN CHILDREN LIVING IN EDUCATIONAL AND REHABILITATION CENTERS - N.L. Chukhray; D.V. Danylyuk (Український стоматологічний альманах)
Assessment of periodontal tissues state in children from educational and rehabilitation centers aimed at further monitoring and development of therapeutic and preventive measures is an urgent task of modern dentistry.